Tackling HIV-related Stigma and Discrimination in South Asia - Stangl, Anne (World Bank, 2012)
Although HIV prevalence in South Asia is relatively low, the epidemic is growing among marginalized groups, including sex workers, injection drug users, men who have sex with men, and transgender communities. Despite prevention and other efforts to reduce high-risk behaviors such as unprotected sex, buying and selling of sex, and injecting drug use, HIV vulnerability and risk remain high. This problem is partly due to a widespread failure to respond adequately to key social drivers of HIV: stigma and discrimination. Stigmatizing attitudes in the general population and discriminatory treatment by actors ranging from health providers to local policy makers intensify the marginalization of vulnerable groups at highest risk, driving them further from the reach of health services and much-needed prevention, treatment, care, and support. Daily harassment and abuse also cause health problems and adversely affect mental health, thereby leading to depression, social isolation, and an array of adverse socioeconomic outcomes related to HIV and AIDS. The South Asia Region Development Marketplace1 (SARDM) took an innovative and unique approach to addressing these gaps and needs through its 2008 development marketplace, "tackling HIV and AIDS stigma and discrimination." Part one of this reports describes key findings and lessons learned that emerged across the 26 implementers. Part two contains case studies for six of the implementers, offering a more in-depth look at the lessons and challenges of intervening against stigma and discrimination. Part three provides summaries of all 26 projects.